Efektivitas Problem-Based Learning Menggunakan Pre-Lecture Quiz Terhadap Keterampilan Berpikir Kritis - Nabillah Ulfah Arif; Neti Afrianis (LPPM Universitas Negeri Jakarta, 2024)
This research aimed at finding out whether Problem Based Learning with Pre-Lecture Quiz was effective or not in increasing student critical thinking skill. This research was instigated with the learning taking place tended to be centered on the teacher and made students passive. Students need to be actively involved in the learning process for effective and meaningful learning. Quantitative method was used in this research with quasi-experimental approach and pretest-posttest control group design. The samples were the eleventh-grade students of MIPA 5 as the control group and the students of MIPA 6 as the experimental group The techniques of analyzing data were t-test to find out the difference of student critical thinking skill and N-gain test to find out the effectiveness level. The research findings showed that (1) the score signifigansi of t-test 0.000 was lower than 0.05, so H0 was rejected and Ha was accepted. The N-gain score of the experimental group was 76.8%, it was on effective category, the score of control group was 62%, and it was on effective enough category; and (2) The indicators of students' critical thinking skills in the experimental class were higher than the control class, especially in the indicators of strategy and tactics with a percentage of 84.21% and 76.01% respectively. It could be concluded that PBL learning with PLQ was effective in increasing student critical thinking skill